The Legacy of Demak Sultanate’s Da’wah in the Discourse of Islam Nusantara: Separation or Cultural Acculturation? - Sabila Azmi Syahira; Zaimudin; Iin Kandedes (Jurnal Ragam Pengabdian, 2026)
This article critically examines the da'wah legacy of the Demak Bintara Sultanate (1478–1554 CE) as a foundational point for the discourse of Islam Nusantara, particularly in addressing the debate on whether the Islamization strategy undertaken by the Walisongo and the sultans of Demak constitutes cultural separation or cultural acculturation. Employing a social-intellectual historical approach and hermeneutic analysis of primary sources, including babad manuscripts, inscriptions, and mosque architecture, this study identifies three main dimensions of Demak's da'wah legacy: the politico-religious, the socio-cultural, and the epistemological. The findings demonstrate that the Demak Sultanate's da'wah model pursued a dialectical path that neither fully separated from Hindu-Buddhist-Javanese traditions nor uncritically merged with them without Sharia-based filtering. This model formed a synthesis that later became the prototype for the formation of Islam Nusantara. The contribution of this article lies in mapping the intellectual genealogy of Demak's da'wah, which has been insufficiently elaborated in the academic framework of contemporary acculturation theory.